Nickel Cobalt Sulfide core/shell structure on 3D Graphene for supercapacitor application - Lemu Girma Beka (Nature Portfolio, 2017)
Abstract Three-dimensional (3D) core/shell structure of nickel cobalt sulfide is nano-engineered by using series of hydrothermal steps on a CVD grown graphene for supercapacitor application. This core/shell is composited of NiCo2S4 nanotube (NCS) as core and CoxNi(3−x)S2 (CNS) nanosheets as a shell. The as-synthesized composite exhibits excellent electrochemical properties by using the advantage of NCS nanontube core as superhighway for electron and ion transport, and CNS nanosheets shell as high active area pseudocapacitive material. The 3D graphene layer serves as excellent surface area to support 3D NCS/CNS; moreover, it provides excellent electrical conductivity between nickel foam current collector and the 3D NCS/NCS composite. Using these hybrid advantages the as-synthesized graphene/NCS/CNS composite electrode exhibits high areal capacitance of 15.6 F/cm2 at current density of 10 mA/cm2; excellent cycling stability of 93% after 5000 of cycles and excellent rate capability of 74.36% as current increase from 10 to 100 mA/cm2. Moreover, a prototype of asymmetric device fabricated using graphene/NCS/CNS as positive electrode and RGO as negative electrode exhibits high energy density of 23.9 Wh/kg and power density of 2460.6 W/kg at high operating current of 100 mA. Such high performance electrode material may get great application in future energy storage device.